2021 IEEE International Conference on Autonomous Robot Systems and Competitions (ICARSC) 2021
DOI: 10.1109/icarsc52212.2021.9429770
|View full text |Cite
|
Sign up to set email alerts
|

Wearable gait Analysis LAB as a biomarker of Parkinson’s disease motor stages and Quality of life: a preliminary study

Abstract: Bradykinetic, shuffling and shorter steps are prototypical signs of gait in Parkinson's Disease (PD) and important indicators of Quality of Life (QoL). Advances in wearable technologies enabled their use to objectively evaluate these gait fluctuations complementing the subjective categorical clinical scales usually used by clinicians. This paper aims to study the ability of a wearable gait analysis lab, developed by our team, to serve as a biomarker of PD motor stages and an indicator of patients' QoL. We acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Indeed, the Spearman product-moment correlation analysis showed this tendency by verifying positive/negative values of correlation factor. In turn, while walking, patients with increased postural instability show slower and shorter gait cycles and more locomotion asymmetry and variability [21]. The Spearman correlation analysis showed indeed this effect.…”
Section: Metric ρ-Valuementioning
confidence: 72%
See 1 more Smart Citation
“…Indeed, the Spearman product-moment correlation analysis showed this tendency by verifying positive/negative values of correlation factor. In turn, while walking, patients with increased postural instability show slower and shorter gait cycles and more locomotion asymmetry and variability [21]. The Spearman correlation analysis showed indeed this effect.…”
Section: Metric ρ-Valuementioning
confidence: 72%
“…Gait-associated metrics were estimated based on a pre-identi cation of initial/ nal contact detection using the gait events detection algorithm validated by the authors team in [19]. In addition, the computational method used to estimate most of these metrics was previously validated in [19] showing an acceptable error of ≤ 13,45%, and tested in [21] describing the expected parkinsonian prototypical motor signs. Given patients with higher postural instability tend to present a more cautious behaviour in performing the tasks, which leads to a slower and smaller steps, it is expected a decrease in step/stride length, velocity, cadence and swing time and, in turn, an increase in step/stride time and stance and double support time [8, 9,11,19].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD tend to walk slowly, as observed in (Branquinho et al, 2021), where, e.g., 20 patients performed a mean step duration of ~0.601sec when walking 10 m. When testing the model in the RPi integrated on the wearable device, it was observed that by using TF-Lite environment, in real-time detection, we achieved a ~2.87 fps to capture and identify doors, which is a time-effective performance to detect step changes over real-life scenarios Fig. 6.…”
Section: Tablementioning
confidence: 98%
“…6. Indeed, considering the outcomes measured in (Branquinho et al, 2021), with our solution we have ~2frames in a step time of 0.601sec to identify that the patient is in front of a door and deliver on-demand the proprioceptive cue. Also, the DL model was accurate and efficient in detecting doors in real-life scenarios, as observed in Fig.…”
Section: Tablementioning
confidence: 99%